Phytoplankton Diversity as a Water Quality Bioindicator of Mangrove Ecosystems in the Mangrove Rehabilitation and Mangrove Ecotourism Area of Merdeka Beach Serdang Bedagai - Aulia, Putri; Hutasuhut, Melfa Aisyah (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
This study investigates the diversity and composition of phytoplankton as a bioindicator of water quality in the mangrove ecosystems of Merdeka Beach, Bagan Kuala Village, Serdang Bedagai. Sampling was conducted at three sites representing long-term rehabilitation (2010–2025), recent rehabilitation (2024–2025), and mangrove ecotourism areas. Phytoplankton abundance and diversity were analyzed using ecological indices, including Shannon-Wiener Diversity Index (H’), Trophic Diatom Index (TDI), and Percentage Pollution Tolerance Value (%PTV), alongside physicochemical water parameters. Results indicate spatial variation in water quality and phytoplankton communities. Station 1 showed moderate abundance and high diversity, indicating ecological stability. Station 2 exhibited increased abundance but lower diversity, reflecting transitional conditions. Station 3 demonstrated the highest abundance and pollution-tolerant taxa, consistent with elevated nutrient levels due to human activities. TDI and %PTV values corroborated these findings, identifying Station 3 as hypertrophic and heavily polluted. These results highlight the utility of phytoplankton as sensitive indicators of environmental quality and the effectiveness of rehabilitation efforts. The integration of biotic indices and water parameters provides a robust framework for ongoing ecological monitoring and coastal management strategies, particularly in mangrove ecosystems undergoing anthropogenic pressure and restoration.